Impact of obesity on quality of life, psychological status, and disease activity in psoriatic arthritis: a multi-center study - DURUÖZ, MEHMET TUNCAY; ACER KASMAN, SEVTAP (SPRINGER HEIDELBERG, 2022)
This article aims to evaluate the possible effect of obesity on quality of life, psychological status, and other clinical variables in Psoriatic arthritis (PsA). PsA patients have been recruited by the Turkish League Against Rheumatism-Network from various centers in Turkey in this cross-sectional study. Patients with a body mass index (BMI) >= of 30 kg/m(2) were considered obese. Differences among patients with regard to obesity status were assessed with health-related quality of life measures (PsA Quality of Life Questionnaire [PsAQoL]), psychological status (Hospital Anxiety and Depression Scale [HADS]), and disease activity parameters (the Disease Activity index for PSoriatic Arthritis [DAPSA], Disease Activity Score 28-C-reactive protein [DAS28-CRP], Bath Ankylosing Spondylitis Disease Activity Index [BASDAI], Psoriasis Area and Severity Index [PASI]), physical functions (Ankylosing Spondylitis Functional Index [BASFI], Health Assessment Questionnaire [HAQ], and Health Assessment Questionnaire for the spondyloarthropathies [HAQ-S]). Pain was assessed using visual analog scale of pain (VAS-P), and fatigue was evaluated using visual analog scale of fatigue (VAS-F) and Functional Assessment of Chronic Illness Therapy (FACIT). A total of 1033 patients with PsA, 650 (62.9%) non-obese and 383 (37.1%) obese were included in the study. The PsAQoL, HADS-Anxiety, HADS-Depression, DAPSA, DAS28-CRP, BASDAI, BASFI, HAQ and HAQ-S scores of the obese group were higher than the non-obese group (p < 0.05). VAS-P and PASI scores were similar between group of patients with and without obesity. Obese patients had higher median scores of VAS-F and FACIT than non-obese patients (p < 0.05). Linear regression analysis showed that BMI affects the quality of life, depression, and disease activity. Consequently, obesity has significant associations with higher disease activity, lower QoL, risk of anxiety, depression, and fatigue. Therefore, obesity should also be taken into account in the management of PsA patients.
Keywords: Psoriatic arthritis; Obesity; Quality of life; Anxiety; Depression; Disease activity; HEALTH-ASSESSMENT QUESTIONNAIRE; RHEUMATOID-ARTHRITIS; ANKYLOSING-SPONDYLITIS; METABOLIC SYNDROME; DIABETES-MELLITUS; ANXIETY; RISK; COMORBIDITIES; DEPRESSION; PREVALENCE